Design and Implementation of Integrated Square - Shaped Microstrip Patch Antenna with Slots for Wireless Applications - G. Shankara Bhaskara Rao,; G. Hema Latha,; G.S.G.V. Subbaraju,; Ch. Dindu Karthi,; A. Jnaneswari, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this project we designed a square shaped microstrip patch antenna. The design offers desired and enhanced performance characteristics suitable for various wireless communication systems. The design consists of slots and DGS (Defective Ground Structure). The integration of slots within the square patch structure allows for improved radiation characteristics. The designed antenna operates in two different bands. The antenna designed in 5 iterations. The S11 parameter (Return Loss) of proposed antenna is -24.9dB, gain of the proposed antenna is 3.7dB and the VSWR of the proposed antenna is 1.19. The S11 parameters, gain plots and VSWR plots of the proposed antenna is provided in the paper.
Keywords: FR4 Substrate; Microstrip Patch Antenna; HFSS